Potential of Chinese Yam (Dioscorea polystachya Turczaninow) By-Product as a Feed Additive in Largemouth Bass (Micropterus salmoides): Turning Waste into Valuable Resources - Mingshi Chen; Yang Liu; Xiaoxue Bao; Yuhua Yue; Binbin Tong; Xionghui Yang; Hui Yu; Ying Yang; Yuhong Liu; Yingying Yu (Aquaculture Nutrition)
Chinese yam (Dioscorea polystachya Turczaninow) by-product produced in the water extraction process is commonly directly discarded resulting in a waste of resources and environmental pollution. However, the value of Chinese yam by-product which still contains effective ingredients is far from being fully realized; hence, it has the potential to be a safe and effective feed additive in aquaculture. To investigate the impacts of Chinese yam by-product on growth performance, antioxidant ability, histomorphology, and intestinal microbiota of Micropterus salmoides, juvenile fish (initial weight 13.16±0.05 g) were fed diets supplemented with 0% (control), 0.1% (S1), 0.4% (S2), and 1.6% (S3) of Chinese yam by-product for 60 days. The results showed that no significant difference was found in weight gain, specific growth rate, and survival among all the experimental groups (P>0.05). Feed conversion ratios of the S1 and S3 groups were significantly lower than those in the control group (P<0.05). SOD activity of the S3 group and GSH contents of Chinese yam by-product groups were significantly higher than those in the control group (P<0.05). MDA levels of the S2 and S3 groups were significantly lower than those in the control group and the S1 group (P<0.05). Besides, Chinese yam by-product could protect liver and intestine health, as well as increase the abundance of beneficial bacteria and decrease the abundance of potential pathogens. This study suggests that Chinese yam by-product has the potential to be used as a functional feed additive in aquaculture, providing a reference for efficient recovery and utilization of by-products from plant sources during processing and culturing high-quality aquatic products.